Improving the flame retardance of polyisocyanurate foams by dibenzo[d,f][1,3,2]dioxaphosphepine 6-oxide-containing additives - Lenz, Johannes; Pospiech, Doris; Paven, Maxime; Albach, Rolf W.; Guenther, Martin; Schartel, Bernhard; Voit, Brigitte (Polymers, 2019)
A series of new flame retardants (FR) based on dibenzo[d,f][1,3,2]dioxaphosphepine 6-oxide (BPPO) incorporating acrylates and benzoquinone were developed previously. In this study, we examine the fire behavior of the new flame retardants in polyisocyanurate (PIR) foams. The foam characteristics, thermal decomposition, and fire behavior are investigated. The fire properties of the foams containing BPPO-based derivatives were found to depend on the chemical structure of the substituents. We also compare our results to state-of-the-art non-halogenated FR such as triphenylphosphate and chemically similar phosphinate, i.e. 9,10-dihydro-9-oxa-10- phosphaphenanthrene-10-oxide (DOPO), based derivatives to discuss the role of the phosphorus oxidation state.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dibenzo[d; f][1; 3; 2]dioxaphosphepine 6-oxide; DOPO; Flame retardant; Phospha-Michael addition; Polyisocyanurate